Praca zawodowa a funkcjonowanie rodziny – analizy i refleksje - Tomaszewska-Lipiec , Renata (Studia Edukacyjne, 2017)
The article signals the problems of a complex influence that professional work, one of the key values, has over one’s personal life. This issue seems to be the common area of scientific research for both pedagogy and sociology. Based on the EU27 as well as on Polish research results, a thesis has been formulated that professional work may nowadays be a threat to the functioning of the family.